Entwicklungspolitisches bürgerschaftliches Engagement: Ein Beitrag zur Schärfung der Definition - Christine Blome; Eckhard Priller (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
Das vorliegende Discussion Paper leistet einen Beitrag zur Schärfung der Definition des entwicklungspolitischen Engagements. Es hat den Anspruch, die Diskussion über eine Definition entwicklungspolitischen bürgerschaftlichen Engagements zu eröffnen. Bislang fehlt es an einer speziell auf diesen Bereich ausgerichteten begrifflichen Abgrenzung. Ausgangspunkt der Betrachtung sind vorhandene Definitionen zur Entwicklungspolitik und zum bürgerschaftlichen Engagement. Außerdem werden exemplarische Themenfelder von entwicklungspolitischem Engagement und in der Praxis vorhandene Engagementformen berücksichtigt. Auf dieser Grundlage wird folgender Definitionsvorschlag entwickelt: Entwicklungspolitisches bürgerschaftliches Engagement ist individuelles Handeln, das sich explizit oder implizit am Leitbild der nachhaltigen Entwicklung orientiert und sich für eine Verbesserung der Situation von Menschen in Entwicklungsländern einsetzt. Als Entwicklungsländer werden hier diejenigen Länder bezeichnet, die in der OECD-DAC-Liste aufgelistet sind, d.h. im engeren Sinne sind auch Schwellenländer mit berücksichtigt. ... – – The aim of this discussion paper is to contribute to a definition of citizen engagement in the field of development cooperation. A specific definition of this concept has hitherto been lacking. This discussion paper aims at opening the discussion about what citizen engagement in the field of development cooperation is, means and comprises. The starting point for this consideration is represented by the existing definitions of development cooperation and active citizenship, as well as the issues of engagement in the field of development cooperation and the forms of engagement encountered in practice. The following definition is being proposed: Citizen engagement in the field of development cooperation is individual behaviour that explicitly or implicitly supports the concept of sustainable development and seeks to improve the living conditions of people in developing countries, i.e. countries that receive Official Development Assistance (ODA). Citizen engagement in the field of development cooperation is voluntary in nature and is not intended to achieve personal gain. The focus on the community does not preclude individual benefits in the form of the acquisition of knowledge and competence, the forging and cultivation of social relationships or other non-material advantages. Citizen engagement is mostly carried out in the public domain. Active citizenship in the field of development cooperation may manifest itself either at home or abroad and either within or outside organizations. It reflects the donation of time, money and goods. ...
Keywords: 300